Enhancement of Solasodine Extracted from Fruits of Solanum nigrum L. by Microwave-Assisted Aqueous Two-Phase Extraction and Analysis by High-Performance Liquid Chromatography - Li Lin; Wen Yang; Xing Wei; Yi Wang; Li Zhang; Yunsong Zhang; Zhiming Zhang; Ying Zhao; Maojun Zhao (Molecules, 2019)
Background: Solasodine is a major bioactive ingredient in Solanum nigrum L. that has strong pharmacological characteristics. Therefore, the development of a simple and effective extraction method for obtaining solasodine is highly important. This study aims to provide a rapid and effective method for extracting solasodine from Solanum nigrum L. by microwave-assisted aqueous two-phase extraction (MAATPE). Methods: First, the high-performance liquid chromatography (HPLC) conditions were established for the detection of solasodine. Then, the aqueous two-phase system (ATPS) compositions were examined. On the basis of the results of single-factor experiments, for a better yield, response surface methodology (RSM) was used to optimize influential factors including the extraction temperature, extraction time and liquid-to-solid ratio. Results: The maximum extraction yield of 7.11 ± 0.08 mg/g was obtained at 44 °C, an extraction time of 15 min, and a liquid-to-solid ratio of 42:1 mL/g in the ATPS consisting of EtOH solvent, (NH4)2SO4, and water (28:16:56, w/w/w). The extraction yield of the alkaloid obtained using this method was markedly higher than those of microwave-assisted extraction (MAE) and ultrasonic-assisted extraction (UAE). Conclusions: In this work, solasodine was extracted by MAATPE for the first time and a high yield was obtained. MAATPE is a simple, rapid, and green technique for extraction from medical plants. Thus, the present study will enable the development of a feasible extraction method of active alkaloids from Solanum nigrum L.